The Role of Parents in Preventing Sexual Violence on Elementary School children in Bandung - Ikeu Nurhidayah; Neng Lani Ligina (University of Muhammadiyah Malang, 2018)
Sexual violence in children case happens most in age 6-12 years. Impact of sexual violence in children is post traumatic stress disorder (PTSD) and revictimizations in adulthood. Role of parents in prevention sexual violence is very important because parents is the people closest to the child. The Purpose of this study is to get an overview of parents roles to prevention sexual violence in children at SDN 061 Cijerah Bandung Kulon Bandung. This study used quantitative descriptive method with samples 141 of parents at SDN 061 Cijerah from populations 530 students and used accidental sampling method. The instrument used is a quistionnaire by researcher combined prevention sexual violence based on government program PANTS with role of parents based on BKKBN. Reability of this study has a alfa cronbach of 0,918. Data analysis used with calculate cut of point from each role of parents and categorize to good roles or less good roles. The results of this study showed that of 141 parents in general that is 93,6% had good roles. The role of parents as educators 88,7% parents had good role as educators. For incentive 90,8% had good role as incentive. For role models, 91,5% parents be a good role models. As supervisor 85,1% parents be a good supervisors. For counselor 91,5% parents had good role as counselors. For comunicator 72,3% had good role as comunicators.